Effects of dietary arachidonic acid on growth, immunity and intestinal microbiota of Litopenaeus vannamei under microcystin-LR stress - Duan, Yafei; Lu, Zijun; Zeng, Shimin; Dan, Xueming; Zhang, Jiasong; Li, Yanwei (Aquaculture, 2022)
The harmful effects of microcystin-LR (MC-LR) stress are unavoidable in shrimp culture. Arachidonic acid (AA) is a fatty acid that regulates immune responses in aquatic animals. In this study, we investigated the effects of dietary AA on growth, immunity and intestinal microbiota of Litopenaeus vannamei under MC-LR stress. The shrimp were fed a control diet (non-supplemented with AA) or a AA diet (supplemented with 8.0 g/kg AA) for 56 days, followed by an acute MC-LR stress for 72 h. The results showed that dietary AA improved the growth and feed utilization of the shrimp. Microcystin-LR exposure increased the mRNA expressions of reactive oxygen species modulator 1 (ROMO1), glutathione peroxidase (GPx), caspase-3 (Casp-3), NADPH-cytochrome P450 reductase (NCPR) and sulfotransferase (SULT), but decreased that of catalase (CAT) and cytochrome C (Cytc). Dietary AA supplementation reversed the expressions of ROMO1, CAT, GPx and NCPR to the control level, but still maintained the higher levels of Cytc, Casp-3 and SULT than the control and MC-LR stress groups. Dietary AA could not effectively reverse the changes of intestinal microbial diversity, but it could improve intestinal microbial composition variation induced by MC-LR stress. Specially, dietary AA increased the relative abundances of beneficial bacteria Bacteroides and Lactobacillus, and reversed the changes of pathogenic bacteria Vibrio and Photobacterium induced by MC-LR stress to the control level. The changes of intestinal bacteria were correlated with immune gene expression. These results revealed that dietary AA had a positive effect on L. vannamei resistance to MC-LR stress by modulating immune response and intestinal microbial composition. •Dietary AA modulated the immune responses of the shrimp resistance to MC-LR stress.•Dietary AA altered intestinal microbial composition variation induced by MC-LR stress.•Dietary AA increased the abundance of intestinal beneficial bacteria.•The changes of intestinal bacteria were correlated with immune gene expression.